Symphony of secrets [large type] - Slocumb, Brendan (Random House Large Print, 2023)
When he is asked to authenticate a newly discovered piece from famed twentieth-century composer Frederick Delaney, Bern Hendricks uncovers clues that indicate Delaney may have had help composing his most successful work, which makes him a target of a powerful organization who will stop at nothing to keep their secret hidden.